Consumers' response to price increases: Evidence from gasoline markets - Ilona Tsanko (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Understanding how consumers respond to price increases is key when designing price-related policies. Using microdata on vehicle usage and paid fuel prices, I analyze consumers' response, focusing on three channels of mitigation: distance driven, fuel efficiency, and search. On average, consumers mitigate 38 percent of a price increase through these channels. Reducing distance driven is the primary channel of mitigation. Increased search efforts mitigate up to 11 percent of a price increase. Response levels vary significantly with newer vehicles' owners mitigating up to 88 percent of a price increase, while older vehicle owners achieve can mitigate up to 45 percent.
Keywords: D12; Q41; L91; L98; 330; Demand response; Gasoline prices; Consumers search; Fuel consumption